2017
DOI: 10.1016/j.ajhg.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Large Intragenic Deletion in DSTYK Underlies Autosomal-Recessive Complicated Spastic Paraparesis, SPG23

Abstract: SPG23 is an autosomal-recessive neurodegenerative subtype of lower limb spastic paraparesis with additional diffuse skin and hair dyspigmentation at birth followed by further patchy pigment loss during childhood. Previously, genome-wide linkage in an Arab-Israeli pedigree mapped the gene to an approximately 25 cM locus on chromosome 1q24-q32. By using whole-exome sequencing in a further Palestinian-Jordanian SPG23 pedigree, we identified a complex homozygous 4-kb deletion/20-bp insertion in DSTYK (dual serine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
(34 reference statements)
1
21
1
Order By: Relevance
“…More importantly, the incidence of scoliosis is inconsistent in different species. While we found all dstyk mutant zebrafishes have severe scoliosis, among the seven SPG23 families with mutation of DSTYK reported, only patients in three families have scoliosis 58 . These studies indicate that DSTYK mutation may lead to scoliosis in human, but we currently do not know whether the scoliosis in those patients with DSTYK mutation is related to the direct effect of DSTYK mutation on spine development or secondary to the spastic paraparesis.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…More importantly, the incidence of scoliosis is inconsistent in different species. While we found all dstyk mutant zebrafishes have severe scoliosis, among the seven SPG23 families with mutation of DSTYK reported, only patients in three families have scoliosis 58 . These studies indicate that DSTYK mutation may lead to scoliosis in human, but we currently do not know whether the scoliosis in those patients with DSTYK mutation is related to the direct effect of DSTYK mutation on spine development or secondary to the spastic paraparesis.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies reported that patients with a large intragenic deletion of DSTYK as the genetic basis for Spastic Paraparesis type 23 (SPG23), an autosomal-recessive disorder characterized by progressive spastic paraplegia and skin pigment abnormalities 58 . In fact, melanosomes in skin and hair melanocytes also belong to LROs, and disordered melanosome biogenesis has been found to result in pigment abnormalities 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed exome sequencing in nine individuals from this pedigree (Figure a), two of whom are affected (IV:8 and IV:10). Variant calling was performed with a previously published in‐house pipeline (Lee et al, ). More than 4.9 Gb of sequence was generated per sample, such that >94% of the target exome was present at >20‐fold coverage, and >98% was present at fivefold coverage (Supplementary Tables S1 and S2).…”
Section: Methodsmentioning
confidence: 99%
“…A number of mutation carriers also manifested neurologic phenotypes such as ataxia and epilepsy, suggesting that DSTYK mutation can affect neurologic development (110). It is thus interesting that a recent study reported homozygosity for a rare intragenic deletion that encompasses the last two exons and the 3′ UTR of DSTYK in three unrelated families of Middle-Eastern ancestry with autosomal recessive spastic paraparesis (111). The proband phenotype in one family also included a horseshoe kidney, suggesting that this particular DSTYK mutation can also affect kidney and urinary tract development.…”
Section: Recent Insights From Human Genetic Studiesmentioning
confidence: 99%